2020
DOI: 10.3390/app10030751
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation of Wind Characteristics over Mountainous Valley Bridge Site Considering Improved Boundary Transition Sections

Abstract: To study wind characteristics over mountainous terrain, the Xiangjiang Bridge site was employed in this paper. The improved boundary transition sections (BTS) were adopted to reduce the influence of “artificial cliffs” of the terrain model on the wind characteristics at the bridge site over the mountainous terrain. Numerical simulation and experimental investigations on wind characteristics over mountainous terrain with/without BTS were conducted for different cases, respectively. The research results show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Four cases conducted in this study are shown in Figure 3: original topography (OT), without transition section (WTS), Witozinsky transition curve (WTC), and ramp transition curve (RTC). According to previous studies [17,[23][24][25], the performance of the transition curve was evaluated by comparing the characteristics of the flow after the transition section with incoming flow, and the less differences observed, the better. However, the studies of Kilpatrick et al [1] and Lange et al [10] highlighted the significant effect of the leading edge geometry of the terrain model on the flow behavior over the Bolund Hill.…”
Section: Transition Sectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four cases conducted in this study are shown in Figure 3: original topography (OT), without transition section (WTS), Witozinsky transition curve (WTC), and ramp transition curve (RTC). According to previous studies [17,[23][24][25], the performance of the transition curve was evaluated by comparing the characteristics of the flow after the transition section with incoming flow, and the less differences observed, the better. However, the studies of Kilpatrick et al [1] and Lange et al [10] highlighted the significant effect of the leading edge geometry of the terrain model on the flow behavior over the Bolund Hill.…”
Section: Transition Sectionsmentioning
confidence: 99%
“…Huang et al [17] proposed a comprehensive method to evaluate the performance of several curve transitions including the Hu et al [24] improved theoretical curve. Chen et al [25] considered different weights of speed-up factors, wind attack angle, and turbulence intensity by combining a weighted solution based on the correlation degree to ameliorate the evaluation method for determining the optimal form of the transition section.…”
Section: Introductionmentioning
confidence: 99%
“…Among others, a extreme natural event is certainly represented by windstorms. In this Special Issue, wind load modelling and design is mainly addressed by [6][7][8], while [9] describes the results of a visual test carried out on a suction caisson that support offshore wind turbines. Finally, the last natural hazard analyzed in the Special Issue is snowdrift.…”
Section: Contentsmentioning
confidence: 99%
“…Han et al [5] proposed a multiscale coupling approach suitable for determining the inlet mean wind speed for numerical simulations of the wind field in mountain gorges. In addition to conducting CFD simulations of wind fields in natural topography, researchers have extensively studied wind flow over typical circular hills [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%